EKSITENSI PENDIDIDIKAN ISLAM TERANCAM GLOBALISASI - Muhammad Abdul Salam (Sekolah Tinggi Agama Islam AL Aqidah Al Hasyimiyyah Jakarta, 2019)
Prophet Muhammad Shollahu alaihi wasallam, Allah was delegated to his followers to build up the ethic, morals and a good character. The scientific of education, such as: Plato, Aristoteles and the others had said that the important of education have to be done by the nation. Modernization of Islamic education as the multidimentional that complex. The education as human’s needs as the key to open the modernization. The modernization of Islamic education at perspective’s cultural development and the global’s civilization. The development of sciences and technology with telecommunication and information technology with digital culture. The Islamic education have a strategic’s role in developing the quality of human power development. In globalization era needed a good muslim generation’s profile who have an excellent in iman, science and good deed. Therefore, to face the nation and the state’s life who never determinant, so we need the Islamic education values have to relevant by developing the national’s education.